PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) DALAM UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA - Irma Gusneli; Kartini; Rini Dian Anggraini (Universitas Teknokrat Indonesia, 2026)
This research is motivated by the low mathematics learning outcomes of class VIII-1 students of SMPN 5 Tambang who have not achieved mastery. Based on the initial test, only 11 out of 26 students (40.30%) achieved mastery. This study aims to improve the learning process and increase mathematics learning outcomes through the application of the Team Assisted Individualization (TAI) cooperative learning model. The type of research used is collaborative Classroom Action Research (CAR) which was implemented in two cycles. The subjects of the study were 26 class VIII-1 students. Data were collected through observation and learning outcome tests, then analyzed descriptively qualitatively and quantitatively. The results of the study showed an increase in student learning outcomes, namely from 42.30% in the initial test to 51.53% in cycle I and increased to 88.46% in cycle II. In addition, teacher and student activities also improved at each meeting. Thus, the application of the TAI type cooperative learning model can improve students' mathematics learning outcomes.